2020
DOI: 10.1101/2020.01.08.899229
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A critical re-evaluation of fMRI signatures of motor sequence learning

Abstract: AbstractDespite numerous studies, there is little agreement about what brain changes accompany motor sequence learning, partly because of a general publication bias that favors novel results. We therefore decided to systematically reinvestigate proposed functional magnetic resonance imaging correlates of motor learning in a preregistered longitudinal study with four scanning sessions over 5 weeks of training. Activation decreased more for trained than untrained sequences in pre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 79 publications
(123 reference statements)
6
26
1
Order By: Relevance
“…Previous work demonstrates that delay-period activity in the supplementary motor area (SMA) reflects the identity of upcoming two-element 61 and three-element 62 sequences. A similar segregation has also been found in human subjects performing a key-press task; while there is no evidence for sequence-specific selectivity in the M1 BOLD signal, such selectivity is present in upstream areas 1618 . Using a cycling task, which shares some features with sequence tasks, Russo et al 63 found that M1 activity reflects only the present motor output while SMA activity distinguishes situations that will have different future outputs.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Previous work demonstrates that delay-period activity in the supplementary motor area (SMA) reflects the identity of upcoming two-element 61 and three-element 62 sequences. A similar segregation has also been found in human subjects performing a key-press task; while there is no evidence for sequence-specific selectivity in the M1 BOLD signal, such selectivity is present in upstream areas 1618 . Using a cycling task, which shares some features with sequence tasks, Russo et al 63 found that M1 activity reflects only the present motor output while SMA activity distinguishes situations that will have different future outputs.…”
Section: Discussionsupporting
confidence: 72%
“…Or is chunking a motor skill, in which motor areas generate, holistically, actions that were originally generated separately? Studies of motor cortex report ‘sequence selectivity’: responses that reflect whether an action is performed alone or within a sequence 1015 (although see 1618 ). Sequence selectivity concurs with the hypothesis that chunking is a motor phenomenon, with chunks executed differently from their component elements.…”
Section: Introductionmentioning
confidence: 99%
“…Given the nature of the exponential fit, it is hard to separate the relative contributions of planning efficiency (i.e., benefitting more from a specific window size) and larger horizons to such improvements. Unlike previous studies that examined sequence-specific effects in sequence production (Ariani and Diedrichsen, 2019; Berlot et al, 2020; Verwey, 2001; Verwey and Wright, 2004; Wiestler and Diedrichsen, 2013), here we focused on random sequences. Note that, because of this, the observed practice effects cannot be explained by the formation of specific chunking structures previously proposed as a way to deal with the complexity of planning long movement sequences (Popp et al, 2020; Ramkumar et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…They were instructed to perform the sequences as fast as possible while keeping the overall accuracy >85%. The details of the training protocol, as well as a few other design features (which were not assessed for this paper) have been described elsewhere (Berlot et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…One prominent issue in this debate is whether skilled sequence execution relies on representations in premotor and supplementary motor areas, or whether the sequences are represented in the primary motor cortex (M1) (see Dayan and Cohen, 2011; Berlot et al, 2018 for reviews). We recently conducted a systematic longitudinal 5-week training study (Berlot et al, 2020) employing functional magnetic resonance imaging (fMRI) to assess brain changes with motor sequence learning. We observed no overall change in overall activity with learning in M1, and no changes in the sequence-specific activity patterns.…”
Section: Introductionmentioning
confidence: 99%